Emotional intelligence impact on organizational normative commitment in public sector - Johar, Siti Sarawati; Ibrahim, Nesreen Awada; Isa, Khairunesa (Science & Engineering Research Support Society, 2020)
Employees’ commitment cannot be denied contributing to organizational effectiveness. However, commitment can be affected if no emphasis is placed on psychological factors such as emotional intelligence. This study aims to investigate how emotional intelligence factor can influence the commitment by testing the impact of emotional intelligence on employee normative commitment to the organization. A total of 196 civil servants serving the Local Authority in the southern zone of Peninsular Malaysia were chosen as respondents. Measuring tools used in this study were Emotional Intelligence Self-Description Inventory (EISDI) and Employee Commitment Survey Revised Version (ECS-R). The data was then analysed using a multiple regression analysis in SPSS. The results showed that the emotional intelligence dimension of facilitating thinking with emotion, and dimension of regulation and management of emotion had an impact on normative commitment. From the findings, it also shows that there is relevant influence of two dimensions of emotional intelligence on the normative commitment. Hence, organizations need to realize that emotional intelligence is one of the basic toward formation of attitudes, behaviour, personality and psychological reactions in the organization. In conclusion, efforts to help reinforce positive emotional intelligence among employees need to be addressed in the organization.